2007
DOI: 10.1513/pats.200607-140jg
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling in Granulomatous Lung Disease

Abstract: Granulomatous lung diseases, such as sarcoidosis, hypersensitivity pneumonitis, Wegener's granulomatosis, and chronic beryllium disease, along with granulomatous diseases of known infectious etiologies, such as tuberculosis, are major causes of morbidity and mortality throughout the world. Clinical manifestations of these diseases are highly heterogeneous, and the determinants of disease susceptibility and clinical course (e.g., resolution vs. chronic, progressive fibrosis) are largely unknown. The underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Kveim-like effects have also been observed using non-viable BAL cell extracts or PBMCs derived from sarcoidosis subjects ( Munro and Mitchell, 1987 , Siltzbach and Ehrlich, 1954 , Holter et al, 1992 , Kataria and Holter, 1996 ). Several studies have attempted to identify specific antigens that can discriminate sarcoidosis from healthy subjects or from patients with other granulomatous diseases such as TB ( Hajizadeh et al, 2007 , Chen and Moller, 2007 ). Most of these studies used limited proteomics or genomics to search for tissue antigens ( Hajizadeh et al, 2007 , Richter et al, 1999 , Song et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kveim-like effects have also been observed using non-viable BAL cell extracts or PBMCs derived from sarcoidosis subjects ( Munro and Mitchell, 1987 , Siltzbach and Ehrlich, 1954 , Holter et al, 1992 , Kataria and Holter, 1996 ). Several studies have attempted to identify specific antigens that can discriminate sarcoidosis from healthy subjects or from patients with other granulomatous diseases such as TB ( Hajizadeh et al, 2007 , Chen and Moller, 2007 ). Most of these studies used limited proteomics or genomics to search for tissue antigens ( Hajizadeh et al, 2007 , Richter et al, 1999 , Song et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intradermal injection of the Kveim–Siltzbach suspension (a granulomatous splenic tissue suspension) induces granuloma formation weeks later in sarcoidosis patients suggesting presence of antigen(s) in granuloma tissue and host immunoreactivity to these antigens ( Dubaniewicz, 2010 , Hajizadeh et al, 2007 , Hiramatsu et al, 2003 , Fox et al, 1983 , Munro and Mitchell, 1987 , Siltzbach and Ehrlich, 1954 ). Several studies using state-of-the-art technologies have attempted to identify sarcoidosis antigens or to identify the underlying genetic and environmental factors ( Hajizadeh et al, 2007 , Chen and Moller, 2007 , Zhang et al, 2013 ), yet unifying environmental or genetic factors as initiators of this disease have not been found ( Hunninghake et al, 1999 , Dubaniewicz, 2010 , Eishi et al, 2002 , Oswald-Richter and Drake, 2010 ). These studies reported a number of markers or variations in gene expression signatures, however failed to discriminate between sarcoidosis and other inflammatory or granulomatous diseases ( Koth et al, 2011 , Maertzdorf et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, by immunoscreening the same microarray platform with the sera of culture positive TB subjects, we identified 50 antigens that differentiated between TB, sarcoidosis and healthy controls [33]. Sarcoidosis is a granulomatous disease with striking clinicopathological similarities to TB [34,35]. Proteomic and genomic studies to identify sarcoidosis antigens led to identification of various Mtb related antigens including mycobacterial catalase-peroxidase (mKatG) indicating Mtb as a potential etiologic factor in sarcoidosis [34-41].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcoidosis is a granulomatous disease with striking clinicopathological similarities to TB [34,35]. Proteomic and genomic studies to identify sarcoidosis antigens led to identification of various Mtb related antigens including mycobacterial catalase-peroxidase (mKatG) indicating Mtb as a potential etiologic factor in sarcoidosis [34-41]. The fact that immunoscreening of our T7 phage cDNA library derived from polyA mRNA obtained from BALs and leukocytes of sarcoidosis patients could identify a panel of specific antigens to classify TB from sarcoidosis and healthy controls, suggests of the presence of TB antigens in cDNA library [33].…”
Section: Introductionmentioning
confidence: 99%